Penerapan Kolom Adsorpsi Seri dengan Adsorben Sekam Padi pada Penyisihan Logam Seng (Zn) dari Air Tanah - Shinta Indah; Denny Helard; Dian Ramadhan (Universitas Andalas, 2021)
To increase the performance of continuous adsorption with rice husks as adsorbent in Zn removal from groundwater, a series of fixed bed column was applied. The experiments were carried out at the acrylic columns having diameter of 7 cm, column height of 19.5 cm, bed height of 13.5 cm and flow rate of 2 gpm/ft2 (310 mL/minute) for 540 minutes. The number of columns used were 3 columns arranged in series and the rice husk used were in their original size (1-2 mm). The influent concentration of Zn metal was 7.62 mg/L. The results showed that the use of column adsorption in series increased the removal efficiency of Zn by rice husks, from 33.21% using 1 column to 51.70% with 3 columns. The adsorption capacity of Zn obtained when using 3 columns in series was 3.542 mg/g. In addition, the use of adsorption columns in series can also prolong the saturation of the adsorbent, thereby extending its service life. The overall research results demonstrated that column the adsorption in series with rice husk as an adsorbent has the potential to be applied to remove heavy metals from groundwater.